Perencanaan Jumlah Pengalokasian Produk dan Rute Pengiriman untuk Meminimalkan Biaya Distribusi - Hetty Maulity (Jurnal Teknik Industri, 2008)
Awing & Son represent one of the company which active in effort songkok, handling of inefficient distribution represent main problem in this industry which cause the expense of high product distribution. Of the condition needed by an method to overcome the problem. Alternative of I is Method Transportation represent one of the technique used for the allocation of product to customer by considering the expense of product distribution, capacities of[is source of and request of customer. As for its delivery route is network shipping direct. Especial target of this method is to plan the amount of proposal product allocation so that is later expected by minimization can the expense of product distribution. Alternative of II is Method of Saving Matrix represent one of the method which studying process delivery of goods to customer covering each allocation of retail at vehicle at the same time sort route to pass by vehicle. Especial target of this method is with order allocation every retail at vehicle also minimization can the expense of product distribution. As for its delivery is runs milk with shipping direct. Before we apply transportation method goodness and also method of Saving Matrix, is beforehand done by plotting and forecasting of request data 2 months come. Forecasting of demand by using method matching with result plotting of data, and then selected [by] smallest MAPE. After that result of the forecasting processed by using transportation method and of Saving Matrix. From data processing obtained by result for the allocation of product with transportation method got by retail for the allocation of warehouse of Gresik is to product allocation to Kediri, Ponorogo, Blitar, Banyuwangi, Probolinggo, Situbondo, Sidoarjo, Lamongan, Krian. and Jombang. While for the warehouse of Surabaya product allocation to Malang, Madiun, Jember, Asem Bagus, Madura, Mojokerto, Pasuruan, Krian. By using method of Saving Matrix obtained by cost-saving of distribution equal to Rp130,500.00/period of delivery or equal to 5.17% from Rp2,654,375.00 becoming Rp2,523,875.00.